Varicella zoster virus reactivation during or immediately following treatment of tegumentary leishmaniasis with antimony compounds - Andrea Barbieri Barros; Alex Miranda Rodrigues; Mariane Pereira Batista; Sidney Munhoz Junior; Marcia Hueb; Cor Jesus Fontes (Memorias do Instituto Oswaldo Cruz, 2014)
Antimony compounds are the cornerstone treatments for tegumentary leishmaniasis. The reactivation of herpes virus is a side effect described in few reports. We conducted an observational study to describe the incidence of herpes zoster reactivation during treatment with antimony compounds. The global incidence of herpes zoster is approximately 2.5 cases per 1,000 persons per month (or 30 cases per 1,000 persons per year). The estimated incidence of herpes zoster in patients undergoing antimony therapy is higher than previously reported.